2018
DOI: 10.1177/2059513118784721
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods evaluation of medical tattooing for people who have experienced a burn injury

Abstract: Introduction:There are no existing studies examining the psychological merits of using facial medical tattooing (MT) following burn injury. This study evaluated an MT service supported by The Katie Piper Foundation. It examined accessibility, satisfaction and whether there were improvements in quality of life (QoL).Methods:Thirty-five service-users were invited to participate in a cross-sectional online survey. Twenty-five (71%) responded (24 women; age range = 21–64 years), and of these five (4 women; age ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The study by Yeates et al published in 2018 described that burn scar restoration of the face is a good example. 9 This was a retrospective online survey with patients who received referral to a “tattoo provider” for medical tattooing of hypopigmented facial burn scars. These referrals were made by a charitable foundation focused on comprehensive burn patient care in the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Yeates et al published in 2018 described that burn scar restoration of the face is a good example. 9 This was a retrospective online survey with patients who received referral to a “tattoo provider” for medical tattooing of hypopigmented facial burn scars. These referrals were made by a charitable foundation focused on comprehensive burn patient care in the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…Self-confidence was reported as improved in 22 (88%) patients, mood was reported as improved in 19 (76%) patients, and the ability to socialize was reported as improved in 19 (76%) patients. 9 This study, while retrospective, represents the most complete assessment of patient-reported outcome measurement by including psychological functioning and QoL.…”
Section: Resultsmentioning
confidence: 99%
“…13 Other recent studies show the beneficial impact of medical tattooing on patient body image and psychosocial functioning. [14][15][16] Applications of medical tattooing are expanding, and the field needs professional direction. Elsewhere, we have suggested guidelines and an extensive training curriculum for a medical tattoo assistant profession.…”
Section: Discussionmentioning
confidence: 99%
“…Although complications due to tattoo practices may be a serious health problem, tattoos are also used for medical purposes to camouflage unwanted scars or wound marks and thus allow patients to overcome some negative psychosocial experiences due to burns, postsurgical/postmastectomy scarring, self-harm scars, accidents, and so on [77]. Indeed, scars, especially on visible areas, are disfiguring and stigmatizing with resultant psychosocial implications encompassing anxiety, depression, low self-esteem, avoidance from social activities, and impaired quality of life.…”
Section: Dichotomy Of Medical Complications and Psychological Healingmentioning
confidence: 99%